Novel Hypericin-loaded nanoparticles as a new drug delivery system ameliorate olanzapine-induced early renal injury and oxidative stress: In vitro and in vivo approaches - Abeer M. Abd El-Hameed; Fatimah A.R. AbdulAlim; Amal H. Alsehli; Fadwa A. Elroby (Results in Chemistry)
Olanzapine (OLZ) is considered the recommended medication for treating chronic psychotic illnesses, although OLZ often causes side effects such as kidney injury. Hypericum perforatum, is the natural source of hypericin (HP). Its effectiveness has recently been investigated combined with certain drugs to mitigate their adverse effects. Although the HP medicinal benefits, its bioavailability remains a critical factor that limits its therapeutic applicability by systemic administration. Because of its insolubility in physiologically acceptable fluids, hypericinate salts only scatter as high-molecular-weight colloidal aggregates.Thus, it is important to tackle these challenges and design adequate HP delivery system that boost the loaded drug's solubility in water, enhance its bioavailability, and target the composition to specific sites. The purpose of the current investigation was to formulate a unique oral composition containing HP-loaded silica nanoparticles (HP-SiNPs) as a cytoprotective and antioxidant therapy to enhance the nephroprotective impact of HP on olanzapine-induced nephrotoxicity in male rats.The new formula (HP-SiNPs) was developed and characterized by BET, XRD, SEM, TEM, FTIR, dynamic light scattering, and Raman spectra. The HP-SiNPs release profile, entrapment efficiency, cytotoxicity against the Vero cell line, renal function parameters, antioxidant efficacy, and histological changes in male rats administered with OLZ were all investigated, and they were compared to those of free HP.XRD reveals the development of an HP-silica-based composite with a 275.0 nm particle size, which increases BET surface area and thermal stability. An entrapment efficiency of around 95.61 ± 0.28 %, and a prolonged release of less than 20 % after 12 h were validated by the current results. The cytotoxicity investigation confirmed the formula's safety at both high and low doses. In addition, the in vivo investigation outcomes displayed that HP-SiNPs have a highly significant nephroprotective effect compared to free HP, which is attributed to improving kidney malfunction, renal tissue damage, and boosting antioxidant enzyme activity. According to what we currently know, this investigation is the first to prepare hypericin as an organic compound on silica nanoparticles.In conclusion This study proposed a new synthetic method for preparing a novel HP-silica-based composite. SiNPs have consistently demonstrated their efficacy as a nontoxic nanocarrier for effective HP delivery. The new HP-SiNPs formula is biocompatible and exhibits significant nephroprotective potency in comparison to free HP. It could serve as a possible clinically supportive agent for ameliorating OLZ-induced kidney injury.